Prioritarianism in Education - Erwin Ooghe (Center for Economic Studies and Ifo Institute (CESifo), 2021)
I first summarize and critically discuss the different normative views that are operational in the academic literature on education. Afterwards, I analyze how prioritarians would allocate resources in a dynamic model of skill formation and compare it to utilitarians and Rawlsians. I finish with a brief discussion of several plausible extensions of the resource allocation problem.
Keywords: 330; prioritarianism; education; opportunities versus outcomes; intrinsic versus instrumental value; resource allocation; dynamic skill formation